IMPACT OF THERMAL AND ALTERNATIVE PROCESSING ON PHYTOCHEMICAL QUALITY AND ANTIOXIDANT ACTIVITY OF ALGERIAN MYRTUS COMMUNIS L. FRUIT - TAIBI, Abdeslem; MOKRANI, Abderrahmane; HAMITRI-GUERFI, Fatiha; KADI, Ahcene; TEFFANE, Mohand; ARROUL, Younes; SOBHI, Widad; BOULEKBACHE-MAKHLOUF, Lila; MADANI, Khodir (Food and Feed Research, 2025)
Myrtle (Myrtus communis L.) fruits serve as a crucial reservoir of biologically active and health-protective compounds. These fruits have gained increasing attention for their potential to promote human health due to their diverse range of bioactive phytochemicals. Drying, a common post-harvest treatment, can significantly affect the content and biological efficacy of these compounds. The objective of this study was to investigate the phenolic compound content and antioxidant capacity of myrtle (Myrtus communis L.) fruits as influenced by four different drying methods: FD (freeze drying), SD (sun drying), OD (oven drying), and MWD (microwave drying). Various bioactive compounds were quantified, including total phenolic content (TPC), total flavonoid content (TFC), total flavonol content, total condensed tannin content (CTC), and anthocyanin content (AC). Antioxidant capacity was assessed using four different tests: the DPPH radical scavenging assay (DPPH-RSA), the ABTS radical scavenging assay (ABTS-RSA), the ferric reducing power assay (FRP), and the phosphomolybdenum antioxidant activity assay (PAA). The results indicated that the drying process significantly affected the phytochemical composition and antioxidant capacity of myrtle fruit. Specifically, the freeze-drying (FD) method yielded the highest TPC, TFC, flavonols, CTC, AC, with values of 88.12 mg GAE/g DW, 12.05 mg QE/g DW, 29.99 mg RE/g DW, 75.40 mg CE/g DW, and 4.96 mg CGE/g DW, respectively. Furthermore, FD was associated with the strongest antioxidant activity, demonstrating DPPH-RSA of 143.37 mg TE/g DW, ABTS-RSA of 154.31 mg TE/g DW, FRP of 89.25 AAE/g DW, and PAA of 354.58 TE/g DW, all surpassing the other drying methods. In contrast, sun drying (SD) and oven drying (OD) had a moderate impact on phytochemical composition and antioxidant capacity, while microwave drying (MWD) resulted in the lowest levels of phytochemical content and relatively low antioxidant capacity. Additionally, the correlation test and Principal Component Analysis (PCA) confirmed the effectiveness of FD method in preserving the bioactive compounds and antioxidant activities of myrtle fruits. These findings suggest that FD is the most effective method for maintaining and enhancing the bioactive properties of myrtle fruits.